2021
DOI: 10.1186/s42358-021-00225-0
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic pain in knee osteoarthritis

Abstract: Background This study aimed to investigate the relationship between the neuropathic pain in knee osteoarthritis with the body composition, anthropometric and postural features, physical function, and quality of life. Methods Patients with primary knee osteoarthritis, 50–70 years of age, were included in the study and divided into Group 1 with neuropathic pain and Group 2 with no neuropathic pain according to Douleur Neuropathique-4. The groups were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…We observed several person-level but few foot-level differences between participants with and those without neuropathic pain. Those with neuropathic pain had worse general health (demonstrated by lower SF-12 scores) and greater pain severity, which is consistent with previous reports related to neuropathic pain in individuals with knee OA using a range of health-related quality of life measures (11,13,14) and pain assessment tools (7,8,10,15). Interestingly, we found that although pain severity at rest was higher in those with neuropathic pain, pain during walking was not.…”
Section: Discussionsupporting
confidence: 91%
“…We observed several person-level but few foot-level differences between participants with and those without neuropathic pain. Those with neuropathic pain had worse general health (demonstrated by lower SF-12 scores) and greater pain severity, which is consistent with previous reports related to neuropathic pain in individuals with knee OA using a range of health-related quality of life measures (11,13,14) and pain assessment tools (7,8,10,15). Interestingly, we found that although pain severity at rest was higher in those with neuropathic pain, pain during walking was not.…”
Section: Discussionsupporting
confidence: 91%
“…NS are associated with poor outcomes in knee OA such as increased pain severity, disability [ [40] , [41] , [42] ] and greater functional deficit [ 11 , 43 ]. We found a higher functional limitation in patients with knee OA and NS measured by patient's perception and objectively.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a previous study showed that patients with knee OA who score highly on the painDETECT presented increased pain intensity and greater functional impairment than the remaining cohort [ 14 ]. Moreover, patients with knee OA and NS had longer symptom duration, lower physical function and quality of life [ 42 ]. Therefore, the presence of NS negatively impacts the functional performance of patients with knee OA.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas some might interpret this as evidence against performing prognostic blocks, one large retrospective study found that individuals who experienced >80% relief on GNB obtained better outcomes than those who received between 50% and 79% relief9; this suggests that our 50% cut-off threshold may have been too low. Third, we failed to exclude patients with secondary gain, mild psychopathology, sleep dysfunction, high degrees of disease burden, and the substantial proportion of subjects with possible nociplastic overlay to their KOA, all of whom are more likely to fail interventional treatments 11 28 30 39–44. We also included individuals within a wide age spectrum, as inclusivity enhances generalization.…”
Section: Discussionmentioning
confidence: 99%